The invention of craft - Adamson, Glenn (Bloomsbury, 2013)
"Glenn Adamson's last book, Thinking Through Craft, offered an influential account of craft's position within modern and contemporary art. Now, in his engaging sequel, The Invention of Craft, his theoretical discussion of skilled work is extended back in time and across numerous disciplines. Adamson searches out the origins of modern craft, locating its emergence in the period of the industrial revolution. He demonstrates how craft was invented as industry's "other", a necessary counterpart to ideas of progress and upheaval. In the process, the magical and secretive culture of artisans was gradually dominated through division and explication. This left craft with an oppositional stance, a traditional or anti-modern position. The Invention of Craft ranges widely across media, from lock-making, wood-carving and iron-casting to fashion, architecture and design. It also moves back and forth between periods, from the 18th century to the present day, demonstrating how contemporary practice can be informed through the study of modern craft in its moment of invention"-- Provided by publisher